AI as “Another I”: Journey map of working with artificial intelligence from AI-phobia to AI-preparedness - Lee, Junesoo; Park, Jaehyuk (Organizational Dynamics, 2023)
Artificial intelligence (AI) is becoming an indispensable part of both individual and organizational affairs, in terms of both rhetoric and practices. However, many people who want to (and need to) work with AI may find the advent of this technology overwhelming, as they are not well prepared to do so. This paper aims to address organizational preparedness in the era of AI by introducing two major agendas of AI. Firstly, as a diagnosis of AI-related sentiments that inhibit working with AI, four types of “AI-phobia” are presented: AI-literacy, AI-substitutability, AI-accountability, and AI-implementability. Secondly, the paper outlines methods to address and overcome AI-phobia and effectively work with AI, by presenting a journey map that offers a systematic checklist for AI-related communication and decision-making in organizations.